Novel AQP2 Mutations and Clinical Characteristics in Seven Chinese Families With Congenital Nephrogenic Diabetes Insipidus - Li, Qian; Tian, Dan; Cen, Jing; Duan, Lian; Xia, Weibo (Frontiers in Endocrinology, 2021)
Objective: Mutations in AQP2 (aquaporin-2) lead to rare congenital nephrogenic diabetes insipidus (NDI), which has been limitedly studied in Chinese population. Methods: Twenty-five subjects from seven families with NDI in a department (Beijing, PUMCH) were screened for AQP2 mutations. Clinical characteristics were described and genotype-phenotype correlation analysis was performed. Results: We identified 9 AQP2 mutations in 13 patients with NDI, including 3 novel AQP2 mutations (p.G165D, p.Q255RfsTer72 and IVS3-3delC). Missense mutations were the most common mutation type, followed by splicing mutations, and frameshift mutations caused by small deletion or insertion. The onset-age in our patients was younger than 1 year old. Common manifestations included polydipsia, polyuria (7/7) and intermittent fever (6/7). Less common presentations included short stature (3/7) and mental impairment (1/7). High osmotic hypernatremia and low osmotic urine were the main biochemical features. Dilation of the urinary tract was a common complication of NDI (3/6). Level of serum sodium in NDI patients with compound het AQP2 mutations was higher than non-compound het mutations. Conclusion: In the first and largest case series of NDI caused by AQP2 mutation in Chinese population, we identified 9 AQP2 mutations, including 3 novel mutations. Phenotype was found to correlate with genotypes, revealed by higher level of serum sodium in patients with compound het AQP2 mutations than non-compound het mutations. This knowledge broadens genotypic and phenotypic spectrum for rare congenital NDI and provided basis for studying molecular biology of AQP2.